Sistem Kendali Kecepatan Kendaraan Berdasarkan Kondisi Cuaca Pada Daerah Karawang Dengan Menggunakan Metode Fuzzy Logic - Putra, Habib Alhamdi; Nurpulaela, Lela (Jurnal Ilmiah Wahana Pendidikan, 2023)
Motor vehicles operating on highways can encounter varying weather conditions such as rain, fog, or other adverse weather conditions. Poor weather conditions can significantly affect safety and travel efficiency. Therefore, in this research, we propose a vehicle speed control system that can adjust the speed based on the prevailing weather conditions in the Karawang region. The method employed in this study is Fuzzy Logic. Fuzzy Logic is a control method that allows us to describe the uncertainty and ambiguity associated with complex problems like weather conditions. By utilizing Fuzzy Logic, we can mathematically represent linguistic variables such as "temperatur," and "cloud cover." The proposed vehicle speed control system receives input in the form of weather data from weather sensors installed in the vehicle. This weather data is then processed using predefined rules based on expert knowledge regarding safe speeds under specific weather conditions. The system then generates an output, recommending the appropriate speed for the current weather conditions. To evaluate the system's performance, we conducted simulations using historical weather data from the Karawang region. The simulation results demonstrate that the vehicle speed control system based on weather conditions using the Fuzzy Logic method can effectively adjust the vehicle's speed to match the current weather conditions. By adopting this system, it is expected to enhance driving safety and travel efficiency in the Karawang region